O último grão de areia na ampulheta da vida: poder, política e falecimentos nos periódicos "Correio da Victoria", "Jornal da Victoria" e "O Espírito-Santense" - Scolforo, Jória Motta (2011)
The following dissertation researches news, notes, articles and poetry about deaths published in “Correio da Victoria”, “Jornal da Victoria” and “Espírito-Santense” newspapers, which circulate in the capital of Espírito Santo province, Vitória, on the second half of 19th century. The analysis objective is to explore perceptions and representations of death in capixaba press, with special attention in relations of power between individuals, and social status attributed to some of the deceased. However, some actions before the death are common; unveiled feelings like saudade and friendship; the community participation and involvement in funeral procession; the Catholic Church influence and changes derived from the shock of state’s and church’s power. In the studied period, death was part of everyday life and most of times people didn’t die alone. The community participated and supported the family before and after the death of a relative. Rituals were solemn and formal, and involved particular sounds and tears. Funeral procession were important social events.